The procurement and supply manager's desk reference - Sollish, Fred; Semanik, John (John Wiley & Sons, Inc., 2012)
Written for the worldwide profession of procurement and supply management, this book offers detailed coverage and tips with an eye toward incorporating proactive strategies and best practices. It also features tips on providing value to the organization and helps you identify those strategies that will work for your business for years to come.